Effect of chitosan on the growth and productivity of Solanum lycopersicum - Danny Fernando Pincay-Manzaba (Universidad Central "Marta Abreu" de Las Villas, 2021)
Chitosan is a natural biopolymer that is extracted from the exoskeletons of crustaceans, however, it has different applications at an industrial level, in the agricultural field it is used to improve nutrition and crop yield, also to free plants from stresses that are caused by the environment. The objective of this research was to evaluate the effect of chitosan on the growth and productivity of Solanum lycopersicum L. Four treatments were used, which consisted of three doses of chitosan (100, 500 and 1000 mg L-1) and a control treatment, where the plants were sprayed at 15 and 30 DAT, using a completely randomized block design, with four repetitions. Analysis of variance and independent comparisons of Tukey means were performed. The results show that the high dose (1000 mg L-1) stimulated the values of plant height, stem diameter, number of bunches /plant, number of fruits / plant, equatorial and polar diameter of fruits, fruit weight, as well as the yield in tomato plants